Employment protection in Dutch collective labour agreements - Schils, Trudie (Amsterdam, 2007)
"The Dutch system of employment protection is often perceived as too strict for workers on permanent contracts, because of the large procedural inconveniences, difficulty of dismissal and high severance pay. It is suggested that the system of employment protection lowers labour market flexibility by lowering hiring and firing rates, and increasing the employers’ labour costs. Many parties (e.g. government, employers and trade unions) have opted for reforms of the system in recent years. One of the proposed scenarios is to allow for more differentiation by decentralising employment protection, e.g. regulations in individual or collective labour agreements. At present, however, it is already possible to regulate employment protection on a decentralised level, i.e. in collective labour agreements on a sector or company level. Dutch national labour law is only ? binding, implying that deviations are allowed for in collective labour agreements. Yet, most research on employment protection is on the national provisions and disregards this sector level differentiation. With this study we contribute to the literature by investigating employment protection provisions on a sector level. The level of employment protection on the sector level not only depends on the national level of employment protection, the system of unemployment insurance, but also of union power and collective bargaining strategies pursued by the trade unions. Employment protection provisions might be used as a trading good in collective bargaining, i.e. there might be a trade off with other provisions such as bargained wage development or extra-statutory unemployment insurance. This might lead to sector differences in the level of employment protection found in collective labour agreements. In addition, employment protection affects labour market performance. Hiring and firing rates are expected to be lower at higher levels of employment protection, and the use of temporary contracts as an alternative to regular workers is expected to be higher. To analyse the collective labour agreements, we use the FNV CLA databank and for the analysis of labour market dynamics, we use the online databank of Statistics Netherlands. Our study shows that sector level provisions on employment protection are at or above the national level, which is related to union density. The higher levels of employment protection seem to come at a cost for employers who have higher labour costs, both non-wage and wage costs. Consequently, hiring and firing are indeed lower at higher levels of employment protection. The use of temporary contracts, however, is not higher at higher levels of employment protection, but the opposite is observed. These findings can have important policy implications, especially with respect to the debate in shifting responsibilities, in general but particularly with respect to employment protection regulation, to the sector level."